A new computer program for mass screening of visual defects in preschool children. Issue 4 (1st April 1998) - Briscoe, D; Lifshitz, T; Grotman, M; Kushelevsky, A; Vardi, H; Weizman, S; Biedner, B
Abstract : AIMS: To test the effectiveness of a PC computer program for detecting vision disorders which could be used by non-trained personnel, and to determine the prevalence of visual impairment in a sample population of preschool children in the city of Beer-Sheba, Israel. METHODS: 292 preschool children, aged 4–6 years, were examined in the kindergarten setting, using the computer system and "gold standard" tests. Visual acuity and stereopsis were tested and compared using Snellen type symbol charts and random dot stereograms respectively. The sensitivity, specificity, positive predictive value, negative predictive value, and kappa test were evaluated. A computer pseudo Worth four dot test was also performed but could not be compared with the standard Worth four dot test owing to the inability of many children to count. RESULTS: Agreement between computer and gold standard tests was 83% and 97.3% for visual acuity and stereopsis respectively. The sensitivity of the computer stereogram was only 50%, but it had a specificity of 98.9%, whereas the sensitivity and specificity of the visual acuity test were 81.5% and 83% respectively. The positive predictive value of both tests was about 63%. 27.7% of children tested had a visual acuity of 6/12 or less and stereopsis was absent in 28% using standard tests. Impairment of fusion was found in 5% of children using the computer pseudo Worth four dot test. CONCLUSIONS: The computer program was found to be stimulating, rapid, and easy to perform. The wide availability of computers in schools and at home allow it to be used as an additional screening tool by non-trained personnel, such as teachers and parents, but it is not a replacement for standard testing.